THE ROLE OF HUMAN RESOURCES MANAGEMENT IN THE SUCCESS OF CONSTRUCTION PROJECTS : THE CASE OF IRAQ - Abbas Abdulameer Khalaf (Scholar Express Journals, 2024)
Project management specialists are divided into two camps : those that emphasize the significance of HRM practices in the overall achievement of building projects, and others who doubt the existence of any connection between the two. The objective of our study is to contribute to this ongoing discussion by seeking to validate or refute the presence of a correlation between HRM and the achievement of construction projects in Iraq. Conducting a study in Iraq, which has distinct economic, sociological, political, and religious conditions compared to industrialized countries, will allow us to determine if the connection between Human Resource Management (HRM) and the success of construction projects differs based on the country in which the project is situated. The selection of this study issue is particularly warranted given the scarcity of studies examining the success elements of projects in Iraq, specifically the correlation between human resource management (HRM) and the outcomes of construction projects in Iraq. The findings of our study indicate that HRM is significantly related to the success of construction projects in Iraq. However, compared to the other characteristics examined, HRM exhibits the lowest association with project success. The unexpected outcome can be mostly attributed to the distinctive features of Iraq that impact project management and human resource management within this particular context. Additionally, this could be attributed to the distinct attributes of Human Resource Management (HRM) inside the project setting. To gain a deeper understanding of the correlation between HRM practices and the success of construction projects in Iraq, future study should focus on the unique aspects of HRM within the project context, with a specific emphasis on the project context within developing countries
Keywords: Human Resources Manage; Success; Construction Projects